Mixed messages? Exposure to reports about alcohol's suggested cardiovascular effects and hazardous alcohol use: a cross-sectional study of patients in cardiology care - Paul Welfordsson; Anna-Karin Danielsson; Caroline Björck; Bartosz Grzymala-Lubanski; Matthias Lidin; Ida Haugen Löfman; Sara Wallhed Finn (BMC, 2024)
Abstract Background Hazardous alcohol use is a leading risk factor for disability and death, yet observational studies have also reported reduced cardiovascular disease mortality among regular, low-level drinkers. Such findings are refuted by more recent research, yet have received significant media coverage. We aimed to explore: (1) how patients with cardiovascular diseases access health information about moderate drinking and cardiovascular health; (2) the perceived messages these sources convey, and (3) associations with own level of alcohol use. Methods We conducted a cross-sectional survey of patients in cardiology services at three hospitals in Sweden. The study outcome was hazardous alcohol use, assessed using the AUDIT-C questionnaire and defined as ≥ 3 in women and ≥ 4 in men. The exposure was accessing information sources suggesting that moderate alcohol consumption can be good for the heart, as opposed to accessing information that alcohol is bad for the heart. Health information sources were described using descriptive statistics. Gender, age and education were adjusted for in multiple logistic regression analyses. Results A total of 330 (66.3%) of 498 patients (mean age 70.5 years, 65% males) who had heard that drinking moderately can affect the heart described being exposed to reports that moderate alcohol use can be good for the heart, and 108 (21.7%) met criteria for hazardous alcohol use. Health information sources included newspapers (32.9%), television (29.2%), healthcare staff (13.4%), friends/family (11.8%), social media (8.9%) and websites (3.7%). Participants indicated that most reports (77.9%) conveyed mixed messages about the cardiovascular effects of moderate drinking. Exposure to reports of healthy heart effects, or mixed messages about the cardiovascular effects of alcohol, was associated with increased odds of hazardous alcohol use (OR = 1.67, 95%CI = 1.02-2.74). Conclusions This study suggests that many patients in cardiology care access health information about alcohol from media sources, which convey mixed messages about the cardiovascular effects of alcohol. Exposure to reports that moderate drinking has protective cardiovascular effects, or mixed messages about the cardiovascular effects of alcohol, was associated with increased odds of hazardous alcohol use. Findings highlight a need for clear and consistent messages about the health effects of alcohol.